Plato’s Allegory of the Cave and the Early Christian Concept of ‘True Light’ in the Metaphrasis Psalmorum (138.9-23) of Apollinaris of Laodicea - Manolis Spanakis (Pnyx: Journal of Classical Studies, 2022)
This paper explores the connection and renegotiation of Plato's allegorical simile of the cave and the spiritual exodus from darkness towards 'true light' in Apollinaris' Metaphrasis Psalmorum 138.9-23. First, to inform non-specialists, I outline scholarly views and debates on Plato’s allegory of the Cave and the concept of True light. Second, I compare the fourth-century metaphrase to the Septuagint text and interpret stylistic embellishments in the former as influences of a long tradition of conceptualising light allegorically, together with explorations over the knowability of the divine. Apollinaris' use of the light imagery is, paradoxically, connected with the concept of God as the one who makes darkness bright. Finally, I present Origen and Gregory of Nyssa as pivotal sources to our understanding of the mystical colouring of darkness in the Metaphrasis and the enigmatic verse 12 of the Septuagint's Psalm 138.